Information flow around stock market collapse. (5th July 2018) - Bossomaier, Terry; Barnett, Lionel; Steen, Adam; Harré, Mike; d'Alessandro, Steve; Duncan, Rod
Abstract: Strong correlations among share prices appear during a market transitions. Numerous measures have been proposed to predict crash events, but they all show a trend which peaks at the transition itself. Information flow among share prices peaks before a transition, whereas correlation‐based indices peak at the transition itself. The classic spin model used in physics describes one type of tipping point where there is a peak in information flow located away from the transition point itself and is thus predictive. Information theoretic metrics of this kind have not been applied to prediction in real‐world systems, such as stock markets.